TOTAL PHENOLIC CONTENT AND FREE RADICAL SCAVENGING ACTIVITY OF MIMUSOPS ELENGI L. LEAVES - VINEETA SINGH; PANDEY VN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The motive of the current study was to find out the total phenolic content (TPC) and free radical scavenging (FRS) activity of various solvent extracts of leaves. Methods: Leaves powder was subjected to extraction with different solvents, namely methanol, methanol 80%, ethanol, ethanol 80%, chloroform, acetone, aqueous, and ethyl acetate. Different concentrations of extracts were evaluated for FRS activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and TPC spectrophotometrically by Folin–Ciocalteu method. Results: The results clearly indicate that inhibition concentration of DPPH by leaf extracts was higher in methanol (inhibitory concentration 50=8.74) followed by ethanol >ethanol 80% >methanol 80% > acetone > aqueous > chloroform > ethyl acetate. TPC was higher in methanol (6.2±0.01 mg gallic acid equivalent/g) followed by ethanol > methanol 80% > acetone > aqueous >ethyl acetate > ethanol 80% > chloroform. A significant correlation (y=0.6265x +42.91 R2=0.9756) exists between TPC and FRS activity of methanolic extract. Conclusion: The finding revealed that methanolic extract of leaves contains a significant amount of FRS activity and phenolic compounds compared to other extracts.